Spectrophotometric Determination of Repaglinide and Ezetamibe - Gowri Sankar, D.; Pawar, A.K.M.; Kalyan Sumanth, S.; Madhavi Latha, P.V. (Asian Journal of Chemistry, 2016)
A simple and sensitive visible spectrophotometric method has been developed for the estimation of repaglinide and ezetamibe in pure as well as pharmaceutical formulations. This method is based on the reduced form of the Folin-Ciocalteu reagent under alkaline conditions which exhibits maximum absorbance at 755 and 750 nm for RPG or EZM respectively. Beer's law is obeyed at the concentration range of 2.5–15 μg/mL for repaglinide and ezetamibe. The method has been statistically evaluated and is found to be precise and accurate.